IKIGAI : The Japanese Secret to a Long and Happy Life - Garcia, Hector, 1981- (Hutchinson, 2017)
Bring meaning and joy to all your days with this interntionally bestselling guide to the Japanese concept of ikigai- the happiness of always besing busy-- as revealed by the daily habits of the world's longest-living people - Amazon.com summary. Accor